ANALISIS KESULITAN BELAJAR SISWA KELAS V PADA MATERI PERKALIAN DALAM PEMBELAJARAN MATEMATIKA DI SDI NAIKOTEN 1 - Herolima Lasa Kelen; Febe Priskila Tefa; Lili Missa; Maria Januaria Meo Mesa; Adam Bol Nifu Benu; Habibi Musa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the learning difficulties experienced by fifth-grade students in understanding multiplication at SDI Naikoten 1. The research used a descriptive quantitative approach with 24 students as participants. Data were gathered through questionnaires, classroom observations, and students' written work. A 15-item Likert scale questionnaire was used to measure their level of difficulty. The results show that the average score was 2.61, which falls into the "moderate difficulty" category. Most students (47.22%) experienced moderate difficulty, 33.33% were in the low-difficulty category, and 11.11% faced high difficulty. The study found that students' main challenges came from weak understanding of multiplication concepts, dependence on memorization, frequent mistakes in column multiplication, and limited use of concrete teaching aids. Observations and documentation supported these findings by showing similar patterns of conceptual and procedural errors. Overall, the study concludes that students' difficulties arise from both cognitive and instructional factors. Teachers are encouraged to strengthen conceptual understanding using concrete media, apply differentiated teaching, and conduct ongoing formative assessments to support students with different learning needs.